Correlation and path coefficient analysis for quality and yield contributing parameters in chrysanthemum (Dendranthema grandiflora Tzvelev) - Maya Priya; Deepti Singh; Priyanka Kumari (Annals of Agricultural Research, 2023)
Correlation and path analysis were carried out in twenty genotypes of chrysanthemum (Dendranthema grandiflora Tzvelev) for different quality and yield attributing traits. Among twenty two different parameters to differentiate the contribution made by each parameter in the final flower yield. The results revealed that the genotypic correlation were higher than the phenotypic correlation for the characters obtained, indicating the high heritable nature of the characters. Number of flowers per plant (0.394,0.393) and average fresh weight of flower (0.488, 0.487)were reported highly significant and positive correlation with flower yield per plant and number of ray florets (0.296,0.300) significant and positive correlation with flower yield per plant at both genotypic and phenotypic level, respectively. Since these association are in desirable direction and selection of these traits may ultimately improve the yield. Path coefficient result revealed that characters like number of flowers per plant (1.525, 0.845), number of leaves per plant (0.891, 0.673), average fresh weight of flower (0.754, 0.041) and number of ray florets (0.739, 0.424) were showed direct positive effect towards flower yield per plant at both phenotypic and genotypic level, respectively through facilitates the selection of superior genotypes of chrysanthemum.